Analisis kemampuan pemahaman konsep matematis siswa berdasarkan tipe kepribadian thinking dan feeling dalam menyelesaikan soal aljabar - Oktavia, Thessa; Yulia, Putri (IKIP Siliwangi, 2025)
This research aims to explore the ability to understand mathematical concepts between students with Feeling and Thinking personality types. The qualitative descriptive method with a case study design was applied to four students of SMA N 3 Sungai Full who were selected based on the results of the Myers Briggs Type Indicator (MBTI) test. The instruments used were personality type questionnaires, tests of ability to understand mathematical concepts, and unstructured interviews. Data analysis was carried out using data triangulation to ensure the accuracy and validity of the results. Students' understanding of mathematical concepts in the feeling and thinking aspects on the seven indicators that have been evaluated shows relatively low results, even though their approaches to learning are different. Students with the Feeling type tend to consider more emotional aspects in their understanding, while students with the Thinking type focus more on logic and analysis. This research underscores the importance of approaches tailored to students' personality types to improve their understanding of mathematical concepts.